Questioning the Influence of Sunspots on Amazon Hydrology: Even a Broken Clock Tells the Right Time Twice a Day. Issue 3 (7th February 2018) - Baker, J. C. A.; Gloor, M.; Boom, A.; Neill, D. A.; Cintra, B. B. L.; Clerici, S. J.; Brienen, R. J. W.
Abstract: It was suggested in a recent article that sunspots drive decadal variation in Amazon River flow. This conclusion was based on a novel time series decomposition method used to extract a decadal signal from the Amazon River record. We have extended this analysis back in time, using a new hydrological proxy record of tree ring oxygen isotopes (δ 18 OTR ). Consistent with the findings of Antico and Torres, we find a positive correlation between sunspots and the decadal δ 18 OTR cycle from 1903 to 2012 ( r  = 0.60, p  < 0.001). However, the relationship does not persist into the preceding century and even becomes weakly negative ( r  = −0.30, p  = 0.11, 1799–1902). This result casts considerable doubt over the mechanism by which sunspots are purported to influence Amazon hydrology. Plain Language Summary: In a recent paper, researchers identified a possible connection between the amount of water flowing in the Amazon River and changes in solar activity, measured by number of sunspots. However, the precise details of this relationship and how it might work were not fully understood, and the analysis only covered the 20th century. Amazon tree rings (the annual growth bands visible in the wood of many temperate and tropical trees) have been shown to record information about basin rainfall (and hence Amazon River flow), in the year of their formation, and therefore offer a way to extend the hydrological record back in time. In this study, we used a new tree ring data set from Ecuador to test the link between sunspots and the Amazon water cycle over a 200 year period. We show that the relationship between sunspots and Amazon River flow is not constant over time and suggest it might even arise by chance, just as the hands of a broken clock point to the right time twice a day. This work highlights how proxy climate data sets can sometimes provide more insights than instrumental climate data alone. Key Points: A new proxy record for Amazon River discharge is used to assess the influence of sunspots on Amazon hydrology over a 200 year period The direction of the relationship between sunspots and the hydrological proxy changes over time, casting doubt on the mechanism of control This work shows that long, annually resolved δ 18 OTR proxy records can provide more insights than instrumental data alone